Multiphysics modeling of water transport in high-intensity lignite drying process on pore scale. Issue 21 (2nd November 2018) - Huang, Shaomeng; He, Qiongqiong; Miao, Zhenyong; Wan, Keji; Wan, Yongjiang
ABSTRACT: The understanding of the moisture transfer process in the pore network is quite important to improve the lignite drying efficiency. Scanning electronic microscopy image was used for construction of pore topology closely approximating the true topology of the real lignite for the heat and mass transfer processes on pore scale by COMSOL simulation. Considering the gas‒liquid phase coexistence of water, "Laminar Two-Phase Flow, Phase Field" module and "Liquid Heat Transfer" module were used. The pore size had significant effects on the flow velocity and the larger pores acted as the main pathway for the moisture transport, therefore affected the maximum drying rate. On the other hand, the connection of pores and the throats distribution in the pathway also had a significant effect on the flow velocity, and the moisture between the throats was hard to transfer as a flow, maybe by vapor diffusion. In high-intensity lignite drying process, the moisture vaporization quickly when heated up and vapor pressure was beneficial to keep the pore size and ensure the smooth of moisture flow pathway, thus improving the efficiency of the drying process.